FMN-coated fluorescent iron oxide nanoparticles for RCP-mediated targeting and labeling of metabolically active cancer and endothelial cells - Jayapaul, Jabadurai; Hodenius, Michael; Arns, Susanne; Lederle, Wiltrud; Lammers, Twan; Comba, Peter; Kiessling, Fabian; Gaetjens, Jessica (Biomaterials, 2011)
Riboflavin is an essential vitamin for cellular metabolism and is highly upregulated in metabolically active cells. Consequently, targeting the riboflavin carrier protein (RCP) may be a promising strategy for labeling cancer and activated endothelial cells. Therefore, Ultrasmall SuperParamagnetic Iron Oxide nanoparticles (USPIO) were adsorptively coated with the endogenous RCP ligand flavin mononucleotide (FMN), which renders them target-specific and fluorescent. The core diameter, surface morphology and surface coverage of the resulting FMN-coated USPIO (FLUSPIO) were evaluated using a variety of physico-chemical characterization techniques (TEM, DLS, MRI and fluorescence spectroscopy). The biocompatibility of FLUSPIO was confirmed using three different cell viability assays (Trypan blue staining, 7-AAD staining and TUNEL). In vitro evaluation of FLUSPIO using MRI and fluorescence microscopy demonstrated high labeling efficiency of cancer cells (PC-3, DU-145, LnCap) and activated endothelial cells (HUVEC). Competition experiments (using MRI and ICP-MS) with a 10- and 100-fold excess of free FMN confirmed RCP-specific uptake of the FLUSPIO by PC-3 cells and HUVEC. Hence, RCP-targeting via FMN may be an elegant way to render nanoparticles fluorescent and to increase the labeling efficacy of cancer and activated endothelial cells. This was shown for FLUSPIO, which due to their high T2-relaxivity, are favorably suited for MR cell tracking experiments and cancer detection in vivo.